The U.S. Naval Institute on naval tactics - Hughes, Wayne P (U.S. Naval Institute wheel books, 2015)
In the U.S. Navy ""Wheel Books"" were once found in the uniform pockets of every junior and many senior petty officers. Each small notebook was unique to the Sailor carrying it, but all had in common a collection of data and wisdom that the individual deemed useful in the effective execution of his or her duties. Often used as a substitute for experience among neophytes and as a portable library of reference information for more experienced personnel, those weathered pages contained everything from the time of the next tide, to leadership hints from a respected chief petty officer, to the color coding of the phone-and-distance line used in underway replenishments. In that same tradition, the newNaval Institute Wheel Bookswill provide supplemental information, pragmatic advice, and cogent analysis on topics important to modern naval professionals. Drawn from the U.S. Naval Institute's vast archives that has been accumulated for more than a century, the books will combine articles from the Institute's flagship publicationProceedings, selections from the oral history collection and from Naval Institute Press books to create unique guides on a wide array of relevant professional subjects. Naval tactics were described by Vice Adm. A. K. Cebrowski, a brilliant thinker on the subject of naval warfare, as "the sum of the art and science of the actual application of combat power." Renowned naval tactician Capt. Wayne Hughes called the study of naval tactics as striving "to bring whatever order and understanding is possible out of the chaos of battle." With those words of wisdom serving as the "commander's intent," this collection sheds a bright light on this sometimes dark and mysterious but questionably essential realm, illuminating the principles and concepts of tactics that serve the warrior at the most critical moments.